2014
DOI: 10.14444/1032
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous interspinous distraction device for the treatment of lumbar spinal canal stenosis: Clinical and radiographic results at 2-year follow-up

Abstract: ObjectiveTo evaluate the effectiveness of the In- space (Synthes, Umkirch, Germany) and the correlation between radiographic parameters and clinical outcome in patients with lumbar spinal canal stenosis (LSS).MethodsBetween June 2009 and May 2013, 56 patients with LSS underwent In-space by one senior surgeon. All of the patients were evaluated both clinically and radiographic measurements before the procedure and each visit at the postoperative follow-up. Preoperative and postoperative X-ray imaging was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Epidural fibrosis, sacroiliac joint pain, disc herniation, facet joint pain, and improper surgery have all been proposed as secondary reasons for the unrelenting pain and incapacity in the low back and lower limbs after lumbar spine surgery [26] However, in our results, the pain degree which is quantified by visual analogue scales (VAS) first and categorized is not related to prolonged PLOS. Yet, the mechanism behind lower back pain is still needed to be explored [27][28][29]. The mean age is significantly different between the two groups, which is in line with previous studies [30,31].…”
Section: Discussionsupporting
confidence: 82%
“…Epidural fibrosis, sacroiliac joint pain, disc herniation, facet joint pain, and improper surgery have all been proposed as secondary reasons for the unrelenting pain and incapacity in the low back and lower limbs after lumbar spine surgery [26] However, in our results, the pain degree which is quantified by visual analogue scales (VAS) first and categorized is not related to prolonged PLOS. Yet, the mechanism behind lower back pain is still needed to be explored [27][28][29]. The mean age is significantly different between the two groups, which is in line with previous studies [30,31].…”
Section: Discussionsupporting
confidence: 82%
“…Yingsakmongkol et al found that VAS scores for back pain and leg pain decreased from 6.56 to 2.64 at 1 week postoperatively [27]. Over the subsequent 2 years, patients experienced no significant worsening in VAS for back or leg pain.…”
Section: Next-generation Technologiesmentioning
confidence: 99%
“…Other studies have reported the maintenance of initially improved VAS up to 2 years [21, 27, 36•, 38] or even 3 years [13,23]. Of the latter studies, three are with next-generation products [23,27,38] and three correspond to last-generation [13,21,36•] IPDs. In the preparation of this manuscript, the authors could only find two RCTs in the literature comparing the success of pain reduction between next-vs. last-generation IPDs [23,33].…”
Section: Symptom Reliefmentioning
confidence: 99%